Aqueous Level of ANGPTL4 Correlates with the OCTA Metrics of Diabetic Macular Edema in NPDR - Qing Xu; Chaoju Gong; Lei Qiao; Ruifang Feng; Haiyang Liu; Yalu Liu; Sujuan Ji; Yipeng Zhang; Shuang Wu; Suyan Li (Journal of Diabetes Research)
Purpose. To investigate the aqueous levels of angiogenic factors in nonproliferative diabetic retinopathy (NPDR) patients with diabetic macular edema (DME) and to ascertain their association with optical coherence tomography angiography (OCTA) metrics. Methods. This study enrolled 21 NPDR eyes with DME (NPDR/DME+), 17 NPDR eyes without DME (NPDR/DME-), and 16 diabetic eyes without retinopathy (DWR). Luminex bead-based multiplex array was used to measure the levels of 25 cytokines. OCTA system with a scan area of 3×3 mm was used to measure retinal thickness (RT), retinal volume (RV), superficial vessel density (SVD), deep vessel density (DVD), foveal avascular zone (FAZ) area, perimeter and acircularity index. Results. The levels of ANGPTL4 were significantly different among the three groups (P<0.05), in which NPDR/DME+ group had the highest level and NPDR/DME- group had a higher level than the DWR group (all, P<0.0167). OCTA examination showed that, compared with DWR and NPDR/DME- group, RT and RV increased and the whole/parafoveal DVD decreased in NPDR/DME+ group (all, P<0.05). Meanwhile, NPDR/DME- group had lower parafoveal DVD than the DWR group (P<0.05). Correlation analysis showed that the levels of ANGPTL4 were positively correlated with foveal/parafoveal RT and RV and negatively correlated with whole/parafoveal DVD in NPDR patients (all, P<0.05). As the influencing factor of RT, RV, and DVD, every additional 103 pg/ml of ANGPTL4 was associated with an increase in foveal and parafoveal RT of 4.299 μm and 3.598 μm, respectively. Every additional 106 pg/ml of ANGPTL4 was associated with an increase in foveal and parafoveal RV of 3.371 mm3 and 17.705 mm3, respectively. Every additional 104 pg/ml of ANGPTL4 was associated with a decrease in whole and parafoveal DVD of 1.705% and 1.799%, respectively. Conclusions. The level of ANGPTL4 in aqueous humor of NPDR patients with DME was significantly increased and ANGPTL4 might predict RT, RV, and parafoveal DVD of DME in NPDR patients.